The stress factors and pattern of psychiatric disorders among patients with deliberate self-harm: a study in a tertiary care hospital, Rangpur, Bangladesh - M. Tozammel Hoque; M. Rokeya Satter; M. Mozammel Hoque; M. Saidur Rahman (International Journal of Research in Medical Sciences, 2023)
Background: Deliberate self-harm (DSH) is a complex behavior of maladaptive response to acute and chronic stress, and likely to be suffering from mental health problems as well as co-morbid general medical conditions, including several non-suicidal intentions to suicide. DSH is previously included in suicide. Sir Thomas Browne first used the word ‘suicide’ in 1642 in his religion Medici. The word suicide originated from SUI (of oneself) and CAEDES (murder). According to WHO ‘suicide’ refers to the act of killing oneself intentionally, performed by the person with full knowledge or expectation of the fatal outcome. This study aimed to analyze the stress factors and pattern of psychiatric disorders among patients with DSH. Methods: This descriptive cross-sectional study was conducted at the department of medicine; emergency and OPD, Rangpur medical college, Rangpur, Bangladesh. Study conducted for 1 year; July 2008-June 2009. A total of 116 DSH cases included in study as per inclusion criteria. Convenience sampling technique was undertaken in this study. Result: The majority of patients are in the age group of 20-39 years, with 70% in a psychiatric disorder, and in the 40-59 years age group 7.778% have a psychiatric disorder. Age has a significant relationship with DSH (p<0.001). The 90 patients were suffering from psychiatric disorders among them 61 (67.778%) were suffering from depressive episodes, 12 (13.333%) were suffering from a personality disorder, 8 (8.889%) were suffering from mental and behavioral disorders due to psychoactive substance abuse, 7 (7.778%) were suffering from schizophrenia, 1 (01.111%) were suffering from adjustment disorder, 1 (1.111%) suffering from bipolar disorder. Conclusions: Out of 116 responders 90 (77.586%) were suffering from a psychiatric disorder. Among the patients with psychiatric disorders, 61 (67.778%) patients were found to be suffering from a depressive episode, which was 52.568% of total DSH cases and is an almost treatable disorder.